The Burden of Vibrio sp. Infections – A Scoping Review - Loo, Ke Yan; Law, Jodi Woan-Fei; Tan Loh, Teng Hern; Priyia, Pusparajah; Wong, Sunny Hei; Chan, Kok Gan; Lee, Learn-Han *; Vengadesh, Letchumanan (HH Publisher, 2023)
Vibrios are a group of Gram-negative bacteria ubiquitous in our surrounding environments and responsible for various clinically significant human infections. The three species responsible for human illness are Vibrio cholerae, Vibrio parahaemolyticus, and Vibrio vulnificus. V. cholerae causes cholera which may result in severe dehydration and death without timely treatment, V. parahaemolyticus infection causes gastroenteritis while V. vulnificus infections typically manifest as wound or soft tissue infections with poor prognosis, including amputation or death. Available data on the epidemiology and clinical burden of Vibrio infections were compiled systematically following a literature review, and 149 relevant studies published between 2010 to 2022 were identified. Cholera represents the majority of Vibrio infections, affecting individuals of all ages and gender, while V. parahaemolyticus infections were found to affect mostly adult males. V. vulnificus infections were mostly reported in males over 50 years old with pre-existing co-morbidities. This review's findings may guide planning and implementing preventative measures in affected regions to prevent future Vibrio infections, disease transmission, and major outbreaks.